Cantos e contos do reinado: o acesso ao texto literário por meio das memórias da cultura afro-brasileira - Sarah Satsuki Oliveira Nakano (2019)
This research is based on the need of a new way to deal with sociocultural diversity, including students' experiences, practices and knowledge, so they will be able to perceive themselves as the protagonists of their educational process and literary appropriation, then borders between community and school will be smaller. Thus, the educational project has as the starting points dialogue and students involvement with Reinado (reign), a popular celebration in Cláudio (a city located in the state of Minas Gerais), in which songs and tales reveal a place of resistance and permanence of memory, for the reason that rituals, histories, songs and dramatization are transmitted through oral tradition since the foundation of the Ternos (groups with specific functions). The aim of this experience is to create educational practices able to develop the students autonomy combining experiences they lived with learning from classes, making their knowledge an instrument to read the world and promoting values of citizenship, memory and identity through activities that stimulate researches, interaction, sharing of knowledge and, as the main point, the insertion of the student in the Afro-Brazilian literature and all richness that it has.